The Heirs of the Roman West - Henning, Joachim (Millennium-Studien / Millennium Studies, 2009)
In this collection leading international authorities analyse the structures and economic functions of non-agrarian centres between ca. 500 and 1000 A.D. - their trade, their surrounding settlements, and the agricultural and cultural milieux. The thirty-one papers presented at an international conference held in Bad Homburg focus on recent archaeological discoveries in Central Europe (Vol.1), as well as onthose from southeastern Europe to Asia Minor (Vol. 2).